Evaluation and comparison of dosimetric parameters in PTV for prostate cancer via step and shoot IMRT and 3DCRT - K, Shirani; A, Nedaie H; N, Banaee; H, Hassani; F, Samiei; F, Hajilooei (JOURNAL OF ADVANCES IN PHYSICS, 2014)
The aim of radiation therapy treatment planning is to achieve an optimal balance between delivering a high dose to target volume and a low dose to healthy tissues. The integral dose, conformity and homogeneity indexes, hence, are the important guidance for predicting the radiation effects and choosing the optimal treatment plan. The goal of this study is to compare and investigate the aforementioned parameters in 3DCRT vs. IMRT plan. In order to evaluate dosimetric parameters, data from five patients with prostate cancer, planned by IMRT and 3DCRT were obtained. Prescribed doses for IMRT procedure and 3DCRT were 80Gy and 70 Gy, respectively. Also, the target coverage was achieved with 95% of the prescribed dose to 95% of the PTV in 3DCRT and 95% of the prescribed dose to 98% of the PTV in IMRT method. A total of thirty IMRT and 3DCRT plans were performed for evaluation of dosimetric parameters (for each patient both treatment plans, step and shoot IMRT and 3DCRT with 6, 10 and 18MV energies) were done. The integral dose was calculated as the mean- dose times the volume of the structure. The mean integral dose (ID) received by rectum for 3DCRT was almost 1.01% greater than IMRT while in bladder mean value of ID for IMRT was approximately 1.68% higher than 3DCRT. For PTV in IMRT the ID of target volume had the biggest value (1.14%) compared to that of 3DCRT. Dose conformity in PTV volume in S.A.S and 3DCRT was almost equal. The same outcome was achieved in homogeneity index. The results of this study shows that IMRT method leads to adequate target dose coverage while the prescribed dose for this modality is higher than 3DCRT. IMRT has the ability of increasing the maximum dose to tumor region and improves conformity and homogeneity indexes in target volume and also reduces dose to OAR.